PELATIHAN BAHASA INGGRIS MELALUI LAGU ANAK-ANAK PADA SISWA PAUD RAUDHATUL HASANAH UJUNG BATU KABUPATEN ROKAN HULU RIAU - Asih Ria Ningsih; Rita Arianti (JURNAL MASYARAKAT NEGERI ROKANIA, 2020)
This article describes the advantages and the examples of song to support English language learning process. Children have unique characteristics that could be employed for the supporting factors. One of strategy that teacher should be used to take the students’ attention is song. The use of children’s songs for learning English showed that songs can increase the enthusiasm of children to learn English because learning is fun and does not feel stiff while steps are taken to create learning English is an effective English teachers should consider some aspects, types of songs, number of students, the type of learning activities with the song, and the character of the students.